Fe-Si-B-Nb target

A Fe-Si-B-Nb target with controlled Vickers hardness and composition addresses machining challenges, ensuring smooth surfaces and effective film formation with maintained magnetic and corrosion properties.

JP7605115B2Active Publication Date: 2024-12-24PROTERIAL LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021542884
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-26
Filing Date
2020-08-24
Publication Date
2024-12-24
Estimated Expiration
2040-08-24

AI Technical Summary

Technical Problem

The Fe-Si-B-Nb alloy target is a difficult-to-cut material prone to cracking, chipping, and tool wear during machining, leading to uneven surfaces and potential damage.

Method used

A Fe-Si-B-Nb-based target with a specific compositional formula and Vickers hardness range of 300 to 1100 HV, achieved through powder sintering methods like HIP, ensures smooth machining and prevents cracking and surface irregularities.

Benefits of technology

The solution effectively suppresses tool wear, cracking, and surface irregularities, ensuring a smooth surface finish and preventing abnormal discharge during film formation, while maintaining excellent soft magnetic properties and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605115000001
    Figure 0007605115000001
Patent Text Reader

Abstract

Provided is an Fe-Si-B-Nb-based target, wherein in the machining of the target, wear or breakage of cutting tool tips, the occurrence of cracking or chipping in the body of the target, and the occurrence of unevenness on the surface of the target can be suppressed. The Fe-Si-B-Nb-based target has a compositional formula represented by Fe100-X-Y-Z-aSiXBYNbZMa in terms of atomic ratio, where 15≤X+Y≤35, 0.3≤X / Y≤2.0, 1≤Z≤20, 0<a≤20, and M is at least one element selected from the group consisting of Al, Ti, V, Cr, Mn, Cu, Zr, Mo, W, and C, with the remainder comprising inevitable impurities, and has an average Vickers hardness value of 300-1100 HV as measured at 5 measurement points. The Vickers hardness is preferably in the range of 500-1000 HV.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Fe-Si-B-Nb based target used for forming, for example, a soft magnetic film. [Background technology]

[0002] Various products, including electronic devices, are becoming smaller and lighter, and functional thin films are being applied. For example, Patent Document 1 proposes a soft magnetic film suitable for the core material of magnetic heads and the like, which contains Fe as the main component, a metal element selected from the group consisting of Nb, Nb-Ta, and Ta, a semimetal element selected from the group consisting of B (boron) and B-Si, and N (nitrogen). This soft magnetic film made of Fe-Si-B-Nb-N has excellent soft magnetic properties such as low coercive force, low magnetostriction, and high saturation magnetic flux density, good thermal stability, and is also excellent in corrosion resistance and wear resistance, making it a useful technology.

[0003] The soft magnetic film composed of the above-mentioned Fe-Si-B-Nb-N can be formed by, for example, a sputtering method. Specifically, a method has been proposed in which a Fe-Si-B-Nb alloy containing Fe as a main component, a metal element selected from the group consisting of Nb, Nb-Ta, and Ta, and a metalloid element selected from the group consisting of B and B-Si is used as a target, nitrogen gas is periodically mixed into an inert sputtering gas such as Ar, and a film with a composition modulated in the thickness direction is formed, and then the film is heat-treated. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 2-163911 Summary of the Invention [Problem to be solved by the invention]

[0005] The Fe-Si-B-Nb-based alloy target disclosed in Patent Document 1 is a so-called difficult-to-machine material in which cracks, chips, and peeling of the target body are likely to occur during machining to the shape and dimensions of the target. Therefore, during machining, wear and breakage of the tip of the cutting tool are caused, irregularities are induced on the surface of the obtained target, and in some cases, the target body may be damaged.

[0006] An object of the present invention is to provide an Fe-Si-B-Nb-based target (hereinafter, also simply referred to as "target") that can suppress wear and breakage of the tip of a cutting tool, suppress the occurrence of cracks and chips in the target body, and suppress the occurrence of irregularities on the target surface during machining of the Fe-Si-B-Nb-based target.

Means for Solving the Problems

[0007] The target of the present invention has a composition formula in atomic ratio of Fe 100-X-Y-Z-a Si X B Y Nb Z M a , represented by 15 ≦ X + Y ≦ 35, 0.3 ≦ X / Y ≦ 2.0, 1 ≦ Z ≦ 20, 0 < a ≦ 20, M is one or more elements selected from the group consisting of Al, Ti, V, Cr, Mn, Cu, Zr, Mo, W, and C, the balance consists of inevitable impurities, and the average value of the Vickers hardness measured at 5 measurement points is 300 to 1100 HV.

[0008] It is preferable that the target of the present invention has an average value of the Vickers hardness measured at the above 5 measurement points of 500 to 1000 HV.

Effects of the Invention

[0009] The present invention can suppress wear and breakage of the tip of a cutting tool, suppress the occurrence of cracks and chips in the target body, and suppress the occurrence of irregularities on the target surface during machining of the target. Therefore, it is a useful technology for manufacturing members having excellent soft magnetic properties, thermal stability, corrosion resistance, wear resistance, etc. as described above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The target of the present invention has a Vickers hardness, as specified by JIS Z 2244, in the range of 300 to 1100 HV. The target of the present invention has a specific range of 300 to 1100 HV for the average Vickers hardness measured at five measurement points, so that when machining such as cutting and polishing is performed to obtain the target shape and dimensions, cracks and chips in the target body can be suppressed, and the occurrence of surface irregularities can also be suppressed. Therefore, the target of the present invention has a smooth surface, and can suppress the induction of abnormal discharge and the scattering of nodules to adhere to the treated material. It is preferable that all of the Vickers hardnesses measured at the above five measurement points are in the specific range of 300 to 1100 HV.

[0011] Furthermore, by making the target of the present invention have a Vickers hardness of 300 HV or more, it is possible to suppress the generation of built-up edges in the tips of milling machines, lathes, etc. In other words, the target of the present invention suppresses the gradual increase in the amount of cut of the tip that accompanies the growth of the built-up edge as cutting progresses, and in addition to being able to reduce the dimensional difference of the target between the start and end of cutting, it is also possible to suppress damage to the tip that accompanies peeling of the built-up edge.

[0012] In addition, if a low-hardness portion exists in a region of the target, for example, in the Fe-based alloy matrix phase, only the low-hardness portion may remain or fall off, causing the surface of the eroded region of the target to become rough, which may easily become the starting point of abnormal discharge during film formation. For this reason, the target of the present invention has a Vickers hardness of 300 HV or more. For the same reason as above, the target according to the embodiment of the present invention preferably has a Vickers hardness of 500 HV or more, more preferably 550 HV or more.

[0013] The target of the present invention can suppress the wear amount of chips, for example, in a milling machine or a lathe, by making the Vickers hardness 1100 HV or less. That is, the target of the present invention can suppress the cutting depth of the chip from gradually decreasing with the wear of the chip as the cutting process progresses, and can suppress the increase in the dimensional difference of the target between the start and the end of cutting. In addition, the breakage of the chip can also be suppressed. For the same reason as above, the target according to the embodiment of the present invention preferably has a Vickers hardness of 1000 HV or less, and more preferably 950 HV or less.

[0014] The Vickers hardness referred to in the present invention means that, in addition to suppressing the occurrence of cracks and chips in the target body described above, from the viewpoint of suppressing the occurrence of abnormal discharge during film formation, the average value of the Vickers hardness measured at any five measurement points on the erosion surface of the target is in the range of 300 to 1100 HV. The measurement positions of the Vickers hardness are a total of five positions, namely, any four positions corresponding to the outer peripheral portion and the position corresponding to the central portion in the plane direction of the erosion surface of the target. At this time, the load is 9.8 N and the pressurization time is 10 seconds. In addition, from the viewpoint of making the Vickers hardness of the target according to the embodiment of the present invention 300 to 1100 HV, it is preferable that the metal structure does not have a Fe—Si—B—Nb-based composite compound phase.

[0015] The target of the present invention has a composition formula in atomic ratio of Fe 100-X-Y-Z-a Si X B Y Nb Z M a , which is represented by 15 ≤ X + Y ≤ 35, 0.3 ≤ X / Y ≤ 2.0, 1 ≤ Z ≤ 20, 0 < a ≤ 20. M is one or more elements selected from the group consisting of Al, Ti, V, Cr, Mn, Cu, Zr, Mo, W, and C, and the balance consists of inevitable impurities. The contents of the Si, B, Nb, and M elements can be appropriately adjusted within a range that does not significantly impair the soft magnetic properties, thermal stability, corrosion resistance, and wear resistance. In the target of the present invention, a soft magnetic film with low coercivity can be obtained by setting the total amount of Si and B, i.e., X+Y in the composition formula, to 15 or more. For the same reasons as above, it is preferable that the target according to the embodiment of the present invention has X+Y of 20 or more. Furthermore, the target of the present invention can provide a soft magnetic film with high saturation magnetic flux density by setting X+Y to 35 or less. For the same reasons as above, it is preferable that the target according to the embodiment of the present invention has X+Y of 33 or less.

[0016] The target of the present invention can obtain a thermally stable soft magnetic film by adjusting the ratio of Si to B, i.e., X / Y in the composition formula, to 0.3 or more and 2.0 or less. For the same reasons as above, it is preferable that the target according to the embodiment of the present invention has X / Y of 0.7 or more and 1.6 or less.

[0017] The target of the present invention can obtain a soft magnetic film having corrosion resistance by setting the Nb content, i.e., Z in the composition formula, to 1 or more. For the same reasons as above, it is preferable that the target according to the embodiment of the present invention has Z of 3 or more. Furthermore, in the target of the present invention, a soft magnetic film having a high saturation magnetic flux density can be obtained by setting Z to 20 or less. For the same reasons as above, it is preferable that the target according to the embodiment of the present invention has Z of 10 or less. Incidentally, in the target of the present invention, the same effect as above can be obtained even by substituting a part or all of Nb with Ta.

[0018] The target of the present invention contains more than 0 of one or more elements selected from the group consisting of Al, Ti, V, Cr, Mn, Cu, Zr, Mo, W, and C, i.e., a in the composition formula is greater than 0. As a result, the target of the present invention has a fine nucleus precipitation effect when heat treating an amorphous film formed by sputtering or the like, and can form a microcrystalline film starting from the nucleus, thereby obtaining a soft magnetic film with low coercivity. And, for the same reason as above, it is preferable that the target according to the embodiment of the present invention has a value of 0.5 or more. Furthermore, in the target of the present invention, a soft magnetic film having a high saturation magnetic flux density can be obtained by setting a to 20 or less. For the same reasons as above, it is preferable for the target according to the embodiment of the present invention to set a to 10 or less. For the same reasons as above, it is preferable for the target according to the embodiment of the present invention to set a to 5 or less.

[0019] The target of the present invention can be obtained, for example, by a powder sintering method. Specifically, the target can be obtained by pressure sintering a mixed powder obtained by mixing a pure metal powder and an alloy powder so as to have the above-mentioned component composition. As the alloy powder, in order to prevent the formation of a Fe-Si-B-Nb-based composite compound phase in the metal structure of the target as much as possible, it is preferable to use Fe-Si alloy powder, Fe-B alloy powder, Fe-Nb alloy powder, Fe-Si-B alloy powder, Fe-Si-Nb alloy powder, Fe-B-Nb alloy powder, Fe-Si-M alloy powder, Fe-BM alloy powder, Fe-Nb-M alloy powder, Fe-Si-BM alloy powder, Fe-Si-Nb-M alloy powder, and Fe-B-Nb-M alloy powder. As the pressure sintering, for example, a hot isostatic press (HIP) method, a hot press method, an electric current sintering method, or the like can be applied.

[0020] The pressure sintering is preferably carried out under conditions of a sintering temperature of 700 to 1300° C., a pressing pressure of 30 to 200 MPa, and a time of 1 to 10 hours. By setting the sintering temperature at 700°C or higher, the sintering of the powder can be promoted and the generation of voids can be suppressed, while by setting the sintering temperature at 1300°C or lower, the melting of the powder can be suppressed. When the mixed powder containing the pure metal powder is HIP sintered into the target material of the present invention, the sintering temperature is preferably set to 700 to 900°C in order to suppress the formation of an Fe-Si-B-Nb-based composite compound phase and the generation of voids. Furthermore, by setting the pressure at 30 MPa or more, the progress of sintering can be promoted and the occurrence of voids can be suppressed, while by setting the pressure at 200 MPa or less, the introduction of residual stress into the target during sintering can be suppressed, and the occurrence of cracks after sintering can be suppressed. In addition, by setting the sintering time to 1 hour or more, the progress of sintering can be promoted and the generation of voids can be suppressed, and by setting the sintering time to 10 hours or less, the decrease in manufacturing efficiency can be suppressed. EXAMPLES

[0021] First, Fe powder, Si powder, B powder, Nb powder and Cu powder were prepared. refer to To obtain the target of Example 1, the composition formula in atomic ratio is Fe 66 S 13.5 B 14.5 Nb 5 Cu 1 The powders prepared above were weighed and mixed in a V-type mixer to obtain a mixed powder, so that (X+Y=28, X / Y=0.9, Z=5, a=1). The mixed powder was then filled into a capsule made of soft iron and degassed and sealed at 450°C for 4 hours. The capsule was then pressure-sintered by HIP at 750°C, 122 MPa, and 1 hour to produce a sintered body.

[0022] refer to To obtain the target of Example 2, the composition formula in atomic ratio is Fe 69.5 S 14.2 B 15.3 Cu 1Gas atomized powder and Nb powder were prepared to form the alloy composition. The composition formula in atomic ratio was Fe 66 S 13.5 B 14.5 Nb 5 Cu 1 After weighing the powders prepared above so that (X+Y=28, X / Y=0.9, Z=5, a=1), they were mixed in a V-type mixer to obtain a mixed powder. This mixed powder was then filled into the die of a hot press machine and pressure-sintered at 1000°C, 30 MPa, and 2 hours to produce a sintered body.

[0023] In order to obtain a target of Example 3 of the present invention, Fe powder, Si powder, B powder, Nb powder and Ti powder were prepared, and the composition formula in atomic ratio was Fe 60 S 4.5 B 14.5 Nb 1 Ti 20 The powders prepared above were weighed so that (X+Y=19, X / Y=0.3, Z=1, a=20) and then mixed in a V-type mixer to obtain a mixed powder. This mixed powder was then filled into a soft iron capsule and degassed and sealed at 450°C for 4 hours. The capsule was then pressure-sintered by HIP at 950°C, 122 MPa, and 1 hour to produce a sintered body.

[0024] In order to obtain a target of Example 4 of the present invention, Fe powder, Si powder, B powder, Nb powder and V powder were prepared, and the composition formula in atomic ratio was Fe 44.9 S 23.3 B 11.7 Nb 20 V 0.1 The powders prepared above were weighed so that the ratios were (X+Y=35, X / Y=2.0, Z=20, a=0.1), and then mixed in a V-type mixer to obtain a mixed powder. This mixed powder was then filled into a capsule made of soft iron and degassed and sealed at 450°C for 4 hours. The capsule was then pressure-sintered by HIP at 950°C, 122 MPa, and 1 hour to produce a sintered body.

[0025] In order to obtain a target of Example 5 of the present invention, Fe powder, Si powder, B powder, Nb powder, and Cr powder were prepared, and the composition formula in atomic ratio was Fe 56 S 8 B 17 Nb 9 Cr 10 The powders prepared above were weighed so that (X+Y=25, X / Y=0.5, Z=9, a=10) and then mixed in a V-type mixer to obtain a mixed powder. This mixed powder was then filled into a capsule made of soft iron and degassed and sealed at 450°C for 4 hours. The capsule was then pressure-sintered by HIP at 950°C, 122 MPa, and 1 hour to produce a sintered body.

[0026] In order to obtain a target of Example 6 of the present invention, Fe powder, Si powder, B powder, Nb powder, and Mo powder were prepared, and the composition formula in atomic ratio was Fe 65 S 9 B 6 Nb 15 Mo 5 The powders prepared above were weighed so that (X+Y=15, X / Y=1.5, Z=15, a=5) and then mixed in a V-type mixer to obtain a mixed powder. This mixed powder was then filled into a soft iron capsule and degassed and sealed at 450°C for 4 hours. The capsule was then pressure-sintered by HIP at 950°C, 122 MPa, and 1 hour to produce a sintered body.

[0027] In order to obtain a target of Example 7 of the present invention, Fe powder, Si powder, B powder, Nb powder, Mn powder, Zr powder, and W powder were prepared, and the composition formula in atomic ratio was Fe 58 S 13.5 B 14.5 Nb 5 Mn 3 Zr 3 W 3The powders prepared above were weighed so that (X+Y=28, X / Y=0.9, Z=5, a=9) and then mixed in a V-type mixer to obtain a mixed powder. This mixed powder was then filled into a soft iron capsule and degassed and sealed at 450°C for 4 hours. The capsule was then pressure-sintered by HIP at 950°C, 122 MPa, and 1 hour to produce a sintered body.

[0028] In order to obtain a target for comparison, the composition formula in atomic ratio is Fe 66 S 13.5 B 14.5 Nb 5 Cu 1 A gas atomized powder with the following formula was prepared: (X+Y=28, X / Y=0.9, Z=5, a=1), which was then filled into a soft iron capsule and degassed and sealed at 450°C for 4 hours. The capsule was then pressure sintered by HIP at 950°C, 122 MPa, and 1 hour to produce a sintered body.

[0029] The sintered bodies obtained above were each machined to produce targets. In this case, it was confirmed that no cracks were generated during machining in the targets of invention examples 1 to 7, and no irregularities were generated on the surface after finishing, resulting in a smooth surface. On the other hand, in the comparative example, cracks occurred during machining, and it was not possible to machine the target into the target shape.

[0030] For each of the sintered bodies obtained above, the Vickers hardness was measured at a total of five locations, including four locations corresponding to the outer periphery and one location corresponding to the center, in the planar direction of the surface that would become the erosion surface of the target. The measurement interval was set at a distance that would not affect the measurement between indentations. The Vickers hardness was measured in accordance with JIS Z 2244 using MVK-E manufactured by Akashi Seisakusho Co., Ltd., with a load of 9.8 N and a pressure time of 10 seconds. The results are shown in Table 1.

[0031] [Table 1]

[0032] The targets serving as comparative examples had an average Vickers hardness of more than 1100 HV. In contrast, it was confirmed that the targets of Inventive Examples 1 to 7 all had an average Vickers hardness in the range of 300 to 1100 HV. This confirmed that the target of the present invention is a target that is suppressed from cracking or chipping during machining, and has a smooth surface without unevenness after finish machining. This suggests that the target of the present invention is useful as a target for forming a soft magnetic film that is suppressed from inducing abnormal discharge and from scattering nodules and adhering to the treated material.

Claims

1. The atomic ratio of the composition formula is Fe 100-X-Y-Z-a S X B Y Nb Z M a , 15≦X+Y≦35, 0.3≦X / Y≦2.0, 1≦Z≦20, 0<a≦20, M is one or more elements selected from the group consisting of Al, Ti, V, Cr, Mn, Zr, Mo, W and C, and the balance is unavoidable impurities, and an Fe-Si-B-Nb-based target having an average Vickers hardness measured at five measurement points of 300 to 1100 HV.

2. 2. The Fe-Si-B-Nb based target according to claim 1, wherein an average value of Vickers hardness measured at said five measuring points is 500 to 1000 HV.

Citation Information

Patent Citations

  • Soft magnetic alloy film and manufacture thereof

    JP1990163911A

  • Micro inductor and its manufacturing method

    JP2007221145A

  • Fe-Co ALLOY SPUTTERING TARGET MATERIAL, AND METHOD FOR MANUFACTURING Fe-Co ALLOY SPUTTERING TARGET MATERIAL

    JP2008260969A

  • Fe-BASED SOFT MAGNETIC ALLOY POWDER, METHOD OF MANUFACTURING THE SAME, AND MAGNETIC SHEET USING THE Fe-BASED SOFT MAGNETIC ALLOY POWDER

    JP2010242216A

  • Soft magnetic alloy for magnetic recording, sputtering target material and magnetic recording medium

    JP2012169021A